The level of psychological alienation in a sample of the physically handicapped practicing adapted sports physical activity - CHENATI, Abdelaziz; NATAH , Kamel (sports creativity, 2023)
The current study aimed to find out the degree of psychological alienation among a sample of individuals with motor disabilities who practice adapted physical and sports activities, in addition to identifying the significance of the differences between the sample individuals according to age and educational level. To achieve the objectives of the study, the researcher relied on the descriptive approach. To collect data, a questionnaire consisting of 19 items was designed in its final form to measure the degree of psychological alienation, and it was applied to a sample of 45 individuals distributed according to educational level and age, using a set of statistical methods. The study concluded that the degree of psychological alienation among the respondents is medium, and that there are no statistically significant differences between the respondents due to the educational level variable, in addition to the absence of statistically significant differences due to the age variable